Mengislamkan Turki: Peradaban Tasawuf di Turki-Ottoman Abad ke 13-16 - Fahmi Rizal (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
This article will explain in a descriptive-analytical manner the early development of Sufism or Sufism in the Turkish region, especially in Anatolia in the thirteenth to sixteenth centuries. This study uses historical research by tracing various sources, including books, journals and articles on Sufism and Sufism in Turkey in the thirteenth to sixteenth centuries. The result is that the majority of Sufis and Sufi groups or tarekat originate from Central Asia and Khurasan or Persia. Initially Islam or in this case Sufism and Sufism were spread through individuals, who were usually called by dede, baba, sheikh, mursidorthe bridge, who preached Islam to the lower classes of society. Then, when entering the early fourteenth century, various groups of tarekat entered, which also originated or had their origins in Central Asia or Persia. Apart from that, this article also explains the influence of one of the great Sufis, Ibn Arabi, in the Ottoman Empire in particular. Where his teachings, works and figures were highly valued and appreciated in the Ottoman Empire by the sultans and Ottoman scholars at that time. Artikel ini menjelaskan secara deskriptif-analitis tentang perkembangan awal tasawuf atau sufisme di wilayah Turki, khususnya di Anatolia pada abad ketigabelas hingga keenambelas. Penelitian ini menggunakan penelitian sejarah dengan melacak berbagai sumber baik buku, jurnal dan artikel mengenai sufisme dan tasawuf di Turki abad ketigabelas hingga keenambelas. Hasilnya adalah bahwa mayoritas sufi dan kelompok sufi atau tarekat berasal dari Asia Tengah dan Khurasan atau Persia. Awalnya Islam atau dalam hal ini tasawuf dan sufisme disebarkan melalaui perseorangan, yang biasanya dipanggil dengan dede, baba, syekh, mursid atau pir, yang mendakwahkan Islam kepada masyarakat kelas bawah. Lalu ketika memasuki awal abad keempatbelas masuk berbagai kelompok macam tarekat yang juga berasal atau mempunyai asal usul dari wilayah Asia Tengah atau Persia. Selain itu, di artikel ini juga dijelaskan pengaruh salah satu sufi besar Ibn Arabi di kerajaan Ottoman secara khusus. Di mana ajaran, karya-karyanya hingga sosoknya sangat dihargai dan diapresiasi di kerajaan Ottoman oleh para sultan dan para ulama Ottoman pada saat itu.